2000
DOI: 10.1046/j.1365-246x.2000.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Rayleigh wave amplitudes: attenuation and focusing

Abstract: A large data set of amplitude measurements of minor and major arc Rayleigh waves in the period range 73–171 s is collected. By comparing these amplitudes with the amplitudes of synthetic waveforms calculated by mode summation, maps of lateral variations in the apparent attenuation structure of the Earth are constructed. An existing formalism for predicting the effects of focusing is employed to calculate amplitude perturbations for the same data set. These perturbations are used to construct ‘pseudo‐attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 17 publications
3
57
0
Order By: Relevance
“…Although Gung and Romanowicz (2004) did not include focusing effects in deriving their model QRLW8, subsequent tests indicated that the model was robust with respect to these effects, in agreement with the predictions of Selby and Woodhouse (2000). In particular, Gung and Romanowicz (2004) compared the degree-8 Q m (r) model obtained with and without focusing terms, the latter computed using expression [8] in the 3D elastic model obtained in the first step, and found no significant changes.…”
Section: Current Statusmentioning
confidence: 78%
See 1 more Smart Citation
“…Although Gung and Romanowicz (2004) did not include focusing effects in deriving their model QRLW8, subsequent tests indicated that the model was robust with respect to these effects, in agreement with the predictions of Selby and Woodhouse (2000). In particular, Gung and Romanowicz (2004) compared the degree-8 Q m (r) model obtained with and without focusing terms, the latter computed using expression [8] in the 3D elastic model obtained in the first step, and found no significant changes.…”
Section: Current Statusmentioning
confidence: 78%
“…The applicability of the linear asymptotic approximation to the computation of focusing (eqns [7]-[9]) has been tested by Selby and Woodhouse (2000) on a large data set of Rayleighwave amplitudes on minor and major arcs, in the period range 73-171 s. These authors derived maps of lateral variations of…”
Section: Anelasticity and Focusingmentioning
confidence: 99%
“…As mentioned in the preceding text, amplitude data are also very useful to constrain lateral heterogeneity. Selby and Woodhouse (2000) found that amplitude variations are dominated by anelastic structure for long wavelengths and by elastic structure at short wavelengths. Amplitude information has been used as additional constraints to investigate elastic structure.…”
Section: Other Surface Wave Observablesmentioning
confidence: 99%
“…This strategy led to maps of both even-and odd-degree structure, that were used to construct the first global model of shear attenuation (Romanowicz, 1995). Billien et al (2000) and Selby & Woodhouse (2000; explicitly treated elastic focusing using a linear approximation derived from ray theory (Woodhouse & Wong, 1986). The contribution from focusing to the amplitudes of Rayleigh waves was found to be considerable, even for long periods between 70 s and 170 s. This motivated Billien et al (2000) to jointly invert phase and amplitude measurements of Rayleigh waves for degree-20 maps of phase velocities and attenuation.…”
Section: D Attenuation Modelsmentioning
confidence: 99%